Pendekatan saintifik dalam pengembangan Kurikulum 2013 PAUD - Wikaningtyas, Asih; Nasir, Muhammad (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2024)
The Early Childhood Education (ECE) learning curriculum is a teacher's teaching tool as a learning guide that suits the child's character so that they can compete globally. Innovation is needed in the 2013 Curriculum in the form of curriculum development which is the foundation or basis of education in maximizing aspects of children's development, namely learning with a scientific approach that can stimulate children's thinking abilities, reasoning abilities and analytical abilities. Even though learning through the Independent Curriculum is being promoted, learning with a scientific approach in the 2013 Curriculum is still exciting, especially if presented in the form of educational games which are popular with children. Learning with a scientific approach is very important for children because this learning can increase children's understanding of literacy and numeracy, understand the applicable rules, and have critical reasoning. This research aims to provide information to all ECE educators and parents about the application of learning with a scientific approach in developing the 2013 ECE curriculum. Researchers use library research with a qualitative approach with data collection techniques using documentation. The research subjects are books, articles, or readings and reference sources related to the scientific approach in developing the 2013 ECE Curriculum. The research results found that learning with a scientific approach is very well implemented ECE units because this approach has a child-centred character, develops children's potential, increases children's learning motivation, develops children's attitudes and character, and improves children's communication skills. Apart from that, the scientific approach is designed to actively involve children through the process of asking, observing, gathering information, reasoning or making associations, and communicating it in learning. From the research results, it was concluded that the scientific approach in developing the 2013 ECE curriculum emphasizes the use of scientific methods and approaches that develop critical, creative and innovative thinking skills in early childhood.